Role of the TGF-β cytokine and its gene polymorphisms in asthma etiopathogenesis - Plichta, Jacek; Panek, Michał (Frontiers in Allergy, 2025)
Transforming growth factor beta (TGF-β) is a pluripotent cytokine expressed by all cells of the human body which plays important roles in maintaining homeostasis and allowing for proper individual development. Disturbances in TGF-β signaling contribute to the development of many diseases and disorders, including cancer and organ fibrosis. One of the diseases with the best-characterized correlation between TGF-β action and etiopathogenesis is asthma. Asthma is the most common chronic inflammatory disease of the lower and upper respiratory tract, characterized by bronchial hyperresponsiveness to a number of environmental factors, leading to bronchospasm and reversible limitation of expiratory flow. TGF-β, in particular TGF-β1, is a key factor in the etiopathogenesis of asthma. TGF-β1 concentration in bronchoalveolar lavage fluid samples is elevated in atopic asthma, and TGF-β expression is increased in asthmatic bronchial samples. The expression of all TGF-β isoforms is affected by a number of single nucleotide polymorphisms found in the genes encoding these cytokines. Some of the SNPs that alter the level of TGF-β expression may be associated with the occurrence and severity of symptoms of asthma and other diseases. The TGF-β gene polymorphisms, which are the subject of this paper, are potential diagnostic factors. If properly used, these polymorphisms can facilitate the early and precise diagnosis of asthma, allowing for the introduction of appropriate therapy and reduction of asthma exacerbation frequency.